Pendampingan Masyarakat di Kampung Salak, Kota Sorong: Pelatihan Teknik Pembenihan Ikan Lele Secara Buatan - Mohammad Sayuti; Intanurfehmi B. Hismayasari; Iman Supriatna; Agung Setia Abadi; Ernawati Ernawati; Kadarusman Kadarusman (Penerbit Goodwood, 2021)
Purpose: This community service aimed to improve skills and provide knowledge about catfish artificial spawning techniques in aquaculture at Salak village. Method: The activity was carried out with an interactive method, preceded by a survey of aquaculture location, material provision, accompanied by questions and answers as a problem solver related to catfish artificial spawning techniques and direct practical assistance on artificial spawning techniques. Result: Artificial spawning techniques of catfish result in a faster ovulation process, namely hatching occurs within 18-24 hours so that the availability of seeds is always fulfilled. Conclusions: Training on artificial spawning techniques of catfish provides knowledge to the farmer community about producing catfish seeds quickly to meet consumer demand.